Much Ado About Something? The Abe Government's Reform of Japan's Agricultural Cooperatives (JA). Issue 1 (2nd January 2016) - George Mulgan, Aurelia
ABSTRACT: This article examines the program of agricultural cooperative (JA) reform initiated by the Abe administration in November 2013 and ending with draft legislation approved by the Diet in August 2015 for enactment in April 2016. The government linked JA reform to its broader program of economic reform in several ways: as an important item on the agenda of regulatory reform; as a 'trump card' in the transformation of agriculture into a growth industry; and as a means to strengthen the international competitiveness of the domestic farm industry in order to facilitate further opening of Japan's agricultural market. The Abe administration also had an additional, political objective in accomplishing JA reform – to weaken the political power of JA as one of the country's most formidable and influential pressure groups. This article evaluates the nature of the reform program and its success in achieving its wider economic and political objectives. It argues that the reforms to date are both radical and limited. They are radical because they are unprecedented; on the other hand, they are limited because the extent of the change is relatively circumscribed and therefore its potential to achieve the government's broader economic goals as well as its narrower sectoral goals is relatively modest.